Zinc and copper changes in serum and urine after aerobic endurance and muscular strength exercise - Granell, J. (The Journal of Sports Medicine and Physical Fitness, 2014)
AIM: The role of zinc and copper has been shown essential in the scope of physical exercise. The outcomes of the studies about changes in the concentrations of these elements in blood, in physical effort situations, are sometimes discordant and seem to be related with the type of the exercise done. The purpose of the study was to determine the changes of zinc and copper in serum and urine produced by two kinds of exercise, designing two tests involving different types of physical exertion, which have been defined as aerobic endurance (AE) and muscular strength (MS).